Relational Anthropology for Contemporary Economics A Multidisciplinary Approach - van Nes, Jermo; Nullens, Patrick; van den Heuvel, Steven C. (Ethical Economy, Studies in Economic Ethics and Philosophy,, 2022)
This open access book offers a multidisciplinary dialogue on relational anthropology in contemporary economics. A particular view of the human being is often assumed in economic models, but seldom acknowledged let alone explicated. Addressing this neglected area of research in economic studies, altogether the contributors touch upon the importance and potential of virtues, the notions of freedom and self-love, the potential of simulation models, the dialectics of love, and questions of methodology in constructing a relational anthropology for contemporary economics. The overall result is a highly informative and constructive dialogue, establishing inter alia a research agenda for future collaborative and multidisciplinary study.